Public Perception of Patient Referral Services - Reza Fazaki; Asyiah Simanjorang; Nuraeni Nuraeni (Newinera Publisher, 2026)
Referral is the transfer of responsibility for patient care between health service units, either vertically or horizontally, to ensure appropriate management of health problems. Data from Padang Tiji Health Center showed that patient referrals remained an important issue. In 2018, the number of visits to the health center reached 45,246, while the number of referrals was 6,511. Therefore, this study aimed to identify factors influencing patient referrals at Padang Tiji Health Center in 2020. This study used a cross-sectional survey design involving 100 respondents. The relationship between independent variables and patient referral was analyzed using the Chi-square test with a 95% confidence level and a significance value of p < 0.05. The results of multivariate analysis showed that knowledge had a significant relationship with patient referral, with a p-value of 0.000. Health information also showed a significant relationship, with a p-value of 0.049. Meanwhile, the availability of facilities and infrastructure, availability of human resources, attitudes of health workers, and public perception did not show significant relationships with patient referral. Among all variables, knowledge was found to be the most dominant factor influencing patient referral. This study concludes that knowledge and health information are associated with patient referrals, while facilities, human resources, health worker attitudes, and public perception are not significantly related. It is recommended that Padang Tiji Health Center improve health education and strengthen referral service competence to ensure that referrals are conducted according to established standards and mechanisms.